Facilitation of Reparative Dentin Using a Drug Repositioning Approach With 4-Phenylbutric Acid - Lee, Eui-Seon; Aryal, Yam Prasad; Kim, Tae-Young; Kim, Ji-Youn; Yamamoto, Hitoshi; An, Chang-Hyeon; An, Seo-Young; Lee, Youngkyun; Sohn, Wern-Joo; Jung, Jae-Kwang; Ha, Jung-Hong; Kim, Jae-Young (Frontiers in Physiology, 2022)
For hard tissue formation, cellular mechanisms, involved in protein folding, processing, and secretion play important roles in the endoplasmic reticulum (ER). In pathological and regeneration conditions, ER stress hinders proper formation and secretion of proteins, and tissue regeneration by unfolded protein synthesis. 4-Phenylbutyric acid (4PBA) is a chemical chaperone that alleviates ER stress through modulation in proteins folding and protein trafficking. However, previous studies about 4PBA only focused on the metabolic diseases rather than on hard tissue formation and regeneration. Herein, we evaluated the function of 4PBA in dentin regeneration using an exposed pulp animal model system via a local delivery method as a drug repositioning strategy. Our results showed altered morphological changes and cellular physiology with histology and immunohistochemistry. The 4PBA treatment modulated the inflammation reaction and resolved ER stress in the early stage of pulp exposure. In addition, 4PBA treatment activated blood vessel formation and TGF-𝛽1 expression in the dentin-pulp complex. Micro-computed tomography and histological examinations confirmed the facilitated formation of the dentin bridge in the 4PBA-treated specimens. These results suggest that proper modulation of ER stress would be an important factor for secretion and patterned formation in dentin regeneration.